Political championship: understanding African state effectiveness and Sino-African infrastructure development - Wang, Y (2021)
Why do Chinese-funded and -constructed projects that are similar in nature develop starkly different trajectories in different African states? This question sheds light on the varying state effectiveness in Sub-Saharan Africa. Diverging from existing structural explanations that stress the external agency and institutional argument that emphasizes bureaucratic capacity, I propose a political championship theory to explain variances in African states’ effectiveness to deliver functional infrastructure and policies. I argue that perceived threats from electoral competition generate strong political commitment from the state’s leadership, i.e. a political champion. When a political champion has high authority, their intervention in project implementation generates motivations for bureaucrats and tempers resistance, leading to higher project functionality. To empirically examine the political championship theory and two competing theories: the external agency and the bureaucratic capacity arguments, I trace the process of three Chinese-funded and -constructed railway projects: the Standard Gauge Railway in Kenya, the Addis-Djibouti Railway in Ethiopia, and the Caminho de Ferro de Benguela in Angola. I rely on 250 interviews conducted during 40 weeks of field research from 2017-2019 in Kenya, Ethiopia, Angola, and China. This research contributes to the theoretical debate on state effectiveness by emphasizing individual agency within structural and institutional constraints, a previously understudied area in state effectiveness. This research also challenges the conventional belief and shows that short-term electoral institutions can be as effective as long-term centralized ones in generating leadership commitment to developmental projects or policies. The thorough documentation of three Chinese-sponsored projects in Africa also fills the research gap of Chinese infrastructure projects in developing countries in general—despite its practical significance, limited empirical research studies have explored this subject due to the hard-to-access nature of Chinese actors and projects.